Vitamin D deficiency and stroke - Ali Amiri; Ali Asghar Karimi; Habibolah Zakeri; Leyla Zamani (Fasa University of Medical Sciences, 2012)
Vitamin D comprises a group of fat-soluble pro-hormones, obtained from sun exposure, food, and supplements, and it must undergo two hydroxylation reactions to be activated in the body. Several studies have shown the role of vitamin D in mineral metabolism regulation, especially calcium, phosphorus, and bone metabolism. Some factors such as inadequate vitamin intake and liver or kidney disorders can lead to vitamin D deficiency. Furthermore, vitamin D malnutrition may also be linked to susceptibility to chronic diseases such as heart failure, peripheral artery disease, high blood pressure, cognitive impairment including foggy brain and memory loss, and autoimmune diseases including diabetes type I. Recent research has revealed that low levels of vitamin D increase the risk of cardiovascular-related morbidity (Sato et al., 2004) and mortality (Pilz et al., 2008). Also, hypertension contributes to a reduction in bone mineral density and increase in the incidence of stroke and death. This article reviews the function and physiology of vitamin D and examines the effects of vitamin D deficiency on susceptibility to stroke, as a cardiovascular event, and its morbidity and subsequent mortality.